Uji Antioksidan Fungi Endofitik BS-1 yang Berasosiasi Dengan Bunga Sambiloto (Andrographis Paniculata) Dengan Beras Hitam Sebagai Media Pertumbuhan - Hayuni, Sri; Riga, Riga; Nasra, Edi (Departemen Kimia FMIPA UNP, 2024)
Sambiloto (Andrographis paniculata) is a popular medicinal plant from the Acanthaceae family and andrographolide was the main secondary metabolite with various biological activites including antioxidant. A. paniculata is one of the medicinal plants reported as potential host for endophytic fungi. This study aims to determine the potential of endophytic fungi associated with A. paniculata flower tissue as a source of antioxidant compounds. An isolate from the flowers of A. paniculata was coded as BS-1. Macroscopic observation of BS-1 fungi showed a white mushroom colony with a round shape in the middle and a slightly rough surface. Crude extract of endophytic fungi BS-1 showed the presence of phenolic compounds, terpenoid, steroids, and alkaloids. The antioxidant activity of fungal BS-1 expressed as IC50 and categorized as moderate, with IC50 results in the range of 101-250 ppm.